"Tra strutturalismo e postmodernismo”. La drammaturgia musicale di Corghi alla luce del confronto con Saramago - Graziella Seminara (Itinera, 2020)
In this essay the author reconstructs Azio Corghi’s path to conquest of musical theater and the importance of the confrontation with José Saramago for the development of a personal musical dramaturgy. In addition, the author investigates the main dramaturgical processes adopted by Corghi in the works Blimunda and Divara and finally, he clarifies Corghi’s position towards the aesthetics of postmodernism.